2015
DOI: 10.1098/rspb.2014.2039
|View full text |Cite
|
Sign up to set email alerts
|

Temperature variability and moisture synergistically interact to exacerbate an epizootic disease

Abstract: Climate change is altering global patterns of precipitation and temperature variability, with implications for parasitic diseases of humans and wildlife. A recent study confirmed predictions that increased temperature variability could exacerbate disease, because of lags in host acclimation following temperature shifts. However, the generality of these host acclimation effects and the potential for them to interact with other factors have yet to be tested. Here, we report similar effects of host thermal acclim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 39 publications
9
86
1
Order By: Relevance
“…We included temperature to reflect the potential influence of environmental conditions on infection dynamics [33,34], and body condition to assess whether the endemic infection was more likely to affect individuals with a lower body condition, as reflected by the transition probabilities. Since the body condition is unobserved every time an individual is not caught, we imputed missing values randomly from the lognormal distribution of observed values, after preliminary modelling suggested no time-, site-, sex-or individual-specific pattern in body conditions.…”
Section: (I) Adult Mark-recapture Datamentioning
confidence: 99%
“…We included temperature to reflect the potential influence of environmental conditions on infection dynamics [33,34], and body condition to assess whether the endemic infection was more likely to affect individuals with a lower body condition, as reflected by the transition probabilities. Since the body condition is unobserved every time an individual is not caught, we imputed missing values randomly from the lognormal distribution of observed values, after preliminary modelling suggested no time-, site-, sex-or individual-specific pattern in body conditions.…”
Section: (I) Adult Mark-recapture Datamentioning
confidence: 99%
“…This may contribute to seasonal variation in infection intensity and prevalence, in that skin sloughing reduces Bd load on the ventral skin surface (Chapter 3), and a slower sloughing rate in conjunction with temperature-mediated reduced immune function (Raffel et al 2006) may result in increased susceptibility to disease. Climate change is thought to not only bring changes to average overall temperatures experienced by organisms, but also temperature variability, and recent work has demonstrated that sudden drops in temperature increase the frequency of Bd infection and mortality in moist environments (Raffel et al 2015). This is in line with the temperature variability hypothesis, which states that pathogens acclimate to changes in temperature faster than hosts, owing to their small size and faster metabolic rates (Rohr & Raffel 2010a).…”
Section: How Does Environmental Temperature Affect Skin Sloughing Andsupporting
confidence: 68%
“…The world is experiencing pronounced warming, with 9 of the 10 warmest years in the 135-year period recorded occurring in the twenty-first century (115), which, overall, should make environmental conditions more difficult for B. dendrobatidis to spread. An alternative hypothesis is that increased temperature variability makes hosts more susceptible to B. dendrobatidis because of lags in host acclimation following changes in temperature (116). A reevaluation of decline data from the American tropics suggests that only climate variables associated with temperature variability could account for the spatiotemporal patterns of declines thought to be associated with B. dendrobatidis (49).…”
Section: Temperature Dependence Of Batrachochytrium Dendrobatidis Gromentioning
confidence: 94%